Properties of recombinant cells capable of growing on serine without NhaB Na+/H+ antiporter in Escherichia coli. - Kayahara, T (1992)
Escherichia coli HIT-1 has a mutation in the Na+/H+ antiporter gene, nhaB (P. Thelen, T. Tsuchiya, and E. B. Goldberg, J. Bacteriol. 173:6553-6557, 1991). This strain is not able to utilize serine as a carbon source (T. Ishikawa, H. Hama, M. Tsuda, and T. Tsuchiya, J. Biol. Chem. 262:7443-7446, 1987), because an active NhaB is required to maintain the electrochemical potential of Na+, which drives serine transport via the Na+/serine carrier, the major transport system for serine. We isolated recombinant cells from a cross between strains HIT-1 and Hfr, and these cells were able to grow on serine even though the NhaB Na+/H+ antiporter of the recombinant cells was still defective. We found that the activity of the H+/serine cotransport system, one of the minor serine transport systems in E. coli, was elevated in the recombinant cells. H+/serine cotransport activity was induced by leucine in the recombinant cells more strongly than in strain HIT-1. A kinetic analysis showed that the Vmax, but not the Km, of the transport system was much higher in the recombinant cells than in strain HIT-1 cells.